Pelatihan Penggunaan Media Pemasaran On Line pada UMKM untuk Memperluas Pemasaran - Tobing, Diana Sulianti K. Tobing; Apriono, Markus; Sudarsih, Sudarsih; Gede Krishnabudi, Nyoman (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
The problem of difficulty in finding information regarding the existence of SMEs has become a concern for the government. The government is trying to encourage the development of SMEs towards improving the quality and access to information. The application of digital marketing such as online marketing or e-commerce can be a solution to increase SMEs income. E-commerce is all forms of trade transactions for goods or services carried out electronically. Service activities for SMEs tape in Bondowoso were carried out to provide understanding and skills to the target audience regarding online marketing by utilizing m-commerce. Alternative solutions to the problems faced by tape SMEs include providing assistance in the use of digital marketing using smartphone media. Besides that, SMEs players were also introduced to icons that are generally used in digital marketing features. It is hoped that this community service activity can be a solution to problems in marketing their products and increase the competitiveness of tape SMEs.